Gambaran Pola Asuh Orang Tua dan Perilaku Makan Balita Obesitas di Kabupaten Kebumen: Gambaran Pola Asuh Orang Tua dan Perilaku Makan Balita Obesitas di Kabupaten Kebumen - Karomah, Ulfatul; Suparno, Suparno; Imani, Teguh (Universitas Airlangga, 2024)
Background: The prevalence of overweight among under-five children in Indonesia continues to increase. According to the Indonesian Nutrition Status Survey (SSGI), in 2022, overweight among those was 3.5%, up 1.3% from 2017, while in Kebumen, it was 3.3%, up 0.9% from 2017. Overweight children have a risk of gross motor development disorders 12 times greater than normal. Currently, few health programs focus on addressing children's obesity. Objectives: To understand the parenting and eating behaviors of obese under five children, serving as a reference for the obesity prevention programs in the Regency of Kebumen. Methods: This research was a descriptive study using qualitative with an in-depth interview approach. The informants were ten individuals, consisting of parents of obese children and nutritionists or midwives from local health centers. Results: Most parents did not force their children to eat. They rarely promised anything to make the children willing to eat and often allowed them to choose their preferred foods. They provided the opportunity to increase their food portions. The frequency of main meals for children was 2 to 3 times a day, with formula milk consumption exceeding 8 bottles per day. Additionally, there was a tendency to consume high-calorie and sugary snacks. Children under one year had a history of consistently providing commercially produced complementary feeding starting at the age of 6 months. Conclusions: An education program based on parenting of demandingness and responsiveness, and appropriate eating habits, is crucial to reducing the prevalence of overweight children in the Regency of Kebumen.